Identification of the kinetic parameters of thermal microorganisms inactivation - Bondarchuk, Ivan S.; Perevozkin, Valery P.; Bondarchuk, Sergey S.; Vorozhtsov, Alexander B. (Applied sciences)
A mathematical model for estimating the characteristics of the process of thermal inactivation of vegetative bacterial cells and their spores is presented. The model relates the change rate of the number of living cells as a nonlinear kinetic dependence of the p-th order, and the temperature constant of their inactivation rate is the Arrhenius function. A method for solving the inverse kinetic problem of identifying the parameters of this model from experimental data is proposed. The method is implemented through the minimization of the original functional, which reduces the number of variable parameters. The solution results of inverse problems for determining the kinetic model parameters based on the experimental data of thermal inactivation of bacterial spores B. subtilis and B. anthracis are presented. The obtained parameters are used to solve the direct problems of the dynamics of micro-organism inactivation. The calculation results represent the dependence on the time of the change number of inactivated micro-organisms, and the thermal exposure time for 99% of their deaths at different temperatures. A comparison of the results with other authors' calculations and experimental data confirms the adequacy of the model, the high accuracy of the new solution method and the algorithm for its implementation. The developed model of thermal sterilization can be used for the selective deactivation of pathogens in the food products.